2016
DOI: 10.1002/ccd.26612
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Impact of Stroke Complicating Transcatheter Aortic Valve Implantation: Results From the German TAVIRegistry

Abstract: Stroke complicating TAVI is a serious complication with a clinically relevant incidence even in daily practice leading to a fivefold increase in 30-day-mortality rate, as well as a significant increase in morbidity and disability in patients, who survive this devastating complication. Further research is needed to identify risk factors and ways to reduce stroke after TAVI. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
9
33
0
1
Order By: Relevance
“…Eggebrecht et al showed in a meta-analysis of around 10,000 patients an increased mortality after stroke (>3.5-fold) 19 . Similar results could be found in the German TAVI Registry with a fivefold increase in the in-hospital mortality rate 20 . Differences between first- and new-generation devices have prompted a decrease in CVE appearance.…”
Section: Current Advancessupporting
confidence: 87%
“…Eggebrecht et al showed in a meta-analysis of around 10,000 patients an increased mortality after stroke (>3.5-fold) 19 . Similar results could be found in the German TAVI Registry with a fivefold increase in the in-hospital mortality rate 20 . Differences between first- and new-generation devices have prompted a decrease in CVE appearance.…”
Section: Current Advancessupporting
confidence: 87%
“…Patients with an early CVE (within 30-day) after TAVI had significantly higher mortality at 30-day and 1-year as compared to those without CVE, as shown in several studies ( 5 , 9 , 20 , 21 , 48 50 ). Eggebrecht et al also reported a 3.5 times higher 30-day mortality after stroke in a large meta-analysis.…”
Section: Prognosis Value On Mortality Morbidity and Neurocognitive Fsupporting
confidence: 55%
“…Stroke is a feared complication that has been linked to worse clinical outcomes after TAVR . In fact, embolic stroke is more commonly encountered after TAVR procedures than after conventional surgical AVR, especially comparing outcomes among high‐risk patients .…”
Section: Discussionmentioning
confidence: 99%